2011
DOI: 10.1073/pnas.1105714108
|View full text |Cite
|
Sign up to set email alerts
|

Converting structural information into an allosteric-energy-based picture for elongation factor Tu activation by the ribosome

Abstract: The crucial process of aminoacyl-tRNA delivery to the ribosome is energized by the GTPase reaction of the elongation factor Tu (EF-Tu). Advances in the elucidation of the structure of the EF-Tu/ribosome complex provide the rare opportunity of gaining a detailed understanding of the activation process of this system. Here, we use quantitative simulation approaches and reproduce the energetics of the GTPase reaction of EF-Tu with and without the ribosome and with several key mutants. Our study provides a novel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
131
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(145 citation statements)
references
References 50 publications
11
131
3
Order By: Relevance
“…This mechanistic model is also compatible with recent in silico approaches that predict the catalytic histidine (His84 of Escherichia coli EF-Tu) to be protonated and to be part of an allosteric repositioning of active site residues (38). The authors suggest that for such an allosteric model, the electrostatic interaction between the positively charged histidine and the negatively charged phosphate oxygen at A2662 is important, and they predict that the removal of the latter charge would render GTP hydrolysis pH dependent.…”
Section: A2662 Thiophosphate Diastereomers Both Have Wt Activities Insupporting
confidence: 64%
See 1 more Smart Citation
“…This mechanistic model is also compatible with recent in silico approaches that predict the catalytic histidine (His84 of Escherichia coli EF-Tu) to be protonated and to be part of an allosteric repositioning of active site residues (38). The authors suggest that for such an allosteric model, the electrostatic interaction between the positively charged histidine and the negatively charged phosphate oxygen at A2662 is important, and they predict that the removal of the latter charge would render GTP hydrolysis pH dependent.…”
Section: A2662 Thiophosphate Diastereomers Both Have Wt Activities Insupporting
confidence: 64%
“…It has been shown before that GTP hydrolysis by EF-Tu is pH independent (in the range between pH 6.5 and 8.5) and therefore a primary role of His84 (EF-Tu) as a general base in GTP hydrolysis was excluded (24). However, molecular simulation experiments lead to the suggestion that removal of the negative charge at the phosphate backbone at position A2662 would render the reaction pH dependent (38). Consequently, we decided to test ribosomes carrying the methylphosphonate in the S P configuration in activation of EF-G GTP hydrolysis at different pH values between 7.4 and 6.0.…”
Section: A2662 Thiophosphate Diastereomers Both Have Wt Activities Inmentioning
confidence: 99%
“…26) that the activation involves a histidine (His-84) as a base mechanism. On the other hand, our study that considered the structures of both the active ribosome-bound (EF-Tu′) and inactive (EF-Tu) forms (29) concluded that the His-84 cannot act as a base. We also concluded, using the 1W surfaces, that the direct effect of His-84 on the TS energy is only around 2 kcal/mol and that its effect is thus allosteric.…”
Section: Exploring the Activation Of Ef-tumentioning
confidence: 99%
“…The calculations with the nonpolar (NP) His-84 involved significant instability, due in part to the fact (29,30) that the NP His prefers to be in the EF-Tu structure. Using constraints to keep the NP His in the EF-Tu′ structure gave different results with different constraints, with an increase in the barrier between 10.0 and −2.0 kcal/mol, depending on the constraint and the initial conditions.…”
Section: Exploring the Activation Of Ef-tumentioning
confidence: 99%
“…Process (1) thus corresponds to His84 acting as a general base as proposed by Voorhees et al 8 , while (2) and (3) denote proton transfer to the phosphate group in a substrateassisted mechanism 9,17 in presence of either the ionized or the neutral forms of His84, respectively. The last process (4) does not involve any proton transfer but represents expulsion of metaphosphate from GTP as the limiting case of a fully dissociative path.…”
mentioning
confidence: 99%